Impact of Students’ Exposure to Electronic Media Facilities in Their Homes on Parental Involvement in Management of Students’ Discipline in Public Day Secondary Schools in Kenya - Lydia Mbaki Musau; Ursulla Okoth; Phylisters Matula (European Scientific Journal, ESJ, 2017)
Students’ exposure to electronic media facilities and lack of parental supervision has led to indiscipline among students globally. The purpose of this study was to investigate the impact of students’ exposure to electronic media facilities in their homes on parental involvement in management of students’ discipline in public day secondary schools in Kitui County, Kenya. The hypothesis was: there is no significant difference in means between students’ exposure to electronic media facilities and parental involvement in management of students’ discipline. The sample consisted of 70 principals, 86 Form three class teachers and 354 Form three students. The instruments were questionnaires and focus group discussions. A pre- test was used to validate the questionnaires while a test-re-test method was used to determine reliability. Instruments reliability coefficients were 0.78 for head teachers, 0.75 for class teachers and 0.82 for students’ questionnaires. Descriptive and inferential statistics were utilized for data analysis while the level of significance was set at alpha = 0.05. Based on the results of ANOVA, F (4, 146) =85.548, P = 0.087, the hypothesis was accepted. It was concluded that students’ exposure to electronic media facilities influenced parental involvement in management of students’ discipline although this was not significant. It was recommended that parents should monitor and control the use of electronic media facilities by their children at home to control students’ discipline at school. This paper was drawn out from a study conducted in the year 2016 and 2017 in Kitui County, Kenya.